Pengaruh Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kinerja Pegawai (Dosen) Di Universitas Teknologi Surabaya - Suryati Eko Putro; Lukman Hakim; Muh. Sujudi; Susanto Susanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The aim of this research is to determine the influence of transformational leadership and work discipline on the performance of employees (lecturers) at the Surabaya University of Technology. The population in this study was 38 respondents. The sample used in this research was 38 lecturer respondents at Surabaya University of Technology using a saturated sampling technique because the population was not too large. Researchers process data and analyze data that has been obtained using the SPSS application. This research falls under the umbrella of causal associative research with quantitative methodology. The goal of a causal associative study is to ascertain how two or more factors interact with each other. The instrument measurement scale uses a Likert scale using five levels. The research results show that (1) transformational leadership has no significant effect on employee (lecturer) performance, with a calculated t value of 1.928 < 2.030 and a significance value > 0.05, so H1 is rejected. (2) work discipline has a significant effect on employee (lecturer) performance, with a calculated t value of 3,906 > 2.030 and a significance value < 0.05, so H2 is accepted. (3) transformational leadership and work discipline simultaneously influence employee (lecturer) performance variables at Surabaya University of Technology, with a calculated f value of 491.874 > 2.87 and a significance value < 0.05, so H3 is accepted